Phuyakha Phu Reai Wali: Efforts to Preserve Sentani Lake as a Source of Life Based on Eco-Theological Studies - Maahury, Yane Rosmawati; Irianto, Irianto; Tokoro, Yan Piet (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Lake Sentani, one of the largest lakes in Papua, plays a vital role as a provider of life for the local community but is threatened by human activities. The eco-theology approach emphasizes the moral relationship between humans and nature as a divine mandate. The research method is qualitative and descriptive, with data collected through in-depth interviews with local stakeholders, authorities, and religious figures. Secondary data from previous research and relevant scientific publications are also used. The research findings indicate that maintaining the balance between humans, the lake, and its ecosystem is crucial for the sustainability of Lake Sentani. The local community holds a decisive view of the lake, considering it as “phuyakha phu reai wali” or the lake is my life. This perspective reflects a deep moral connection with the natural environment and their moral responsibility to care for it. Conservation efforts include biodiversity studies, increasing public awareness, and sustainable management. In conclusion, preserving Lake Sentani is not only an ecological issue but also has a strong spiritual dimension. The eco-theological approach highlights the moral responsibility of humans to care for nature as a divine trust. To maintain ecological balance and the well-being of the local community, conservation efforts involving local communities and relevant stakeholders are essential to ensure the lake's sustainability as a source of life.